The Answer to the Question
is below this banner.

Can't find a solution anywhere?

NEED A FAST ANSWER TO ANY QUESTION OR ASSIGNMENT?

You will get a detailed answer to your question or assignment in the shortest time possible.

## Here's the Solution to this Question

1.

$x_m=x_{r+1}x_{m-r}+x_rx_{m-r}$

Prove by the induction

$x_m=x_{m-r}x_{r+2} \ \ \ \ \ \ \ \ \ \ \ \ (*)$

Since $m\geq1$ the base of induction is:

$m=1=>r=0: x_1=x_{1-0}x_{0+2}=1\cdot1=1$

Hence, we proved the base of induction.

Now, we will assume, that the statement (*) is true for every $m Let's prove for $m=k$

Prove by the induction (by r)

$r=0$

$x_k=x_{k-0}x_{0+2} =x_kx_2=x_k$

The induction assumption is that for every $r,$ such that: $0\leq r the statement (*) is true. Let's prove it for $r=r_0.$ We should check the following:

$x_k=x_{k-r_0}x_{r_0+2}=x_{k-r_0}x_{r_0+1}+x_{k-r_0}x_{r_0}$

We can apply the induction assumption to both of the summands in the following way:

For the first summand:

$r_0+1=(r_0-1)+2, k-r_0=(k-1)-(r_0-1)$

We obtain the following(by using the (*)):

$x_{k-r_0}x_{r_0+1}=x_{k-1}$

By applying the induction assumption and (*) to the second summand we obtain:

$x_{k-r_0}x_{r_0}=x_{k-2}$

Thus we should check if:

$x_k=x_{k-1}+x_{k-2}$

This is true.

$x_m=x_{m-r}x_{r+2}=x_{m-r}(x_{r+1}+x_r)=x_{m-r}x_{r+1}+x_{m-r}x_r$

We prove

$x_m=x_{r+1}x_{m-r}+x_rx_{m-r}$

2.

$x_k|x_{kd},$ where $k,d$ are some integers.

Let's use the statement:

$x_m=x_{m-r}x_{r+2}$$x_{kd}=x_{kd-d}x_{d+2}$

By applying this fact $(k-1)$ times, we obtain the following:

$x_{kd} = x_{d} x_{d+2}^{k-1}.$

Thus $(k\geq1): x_k|x_{kd},$ where $k,d$ are some integers.